Synthesis, Characterization, Hydrolytic Stability, Nickel(II) Chloride Complex and Anti-Parasitic Activity of Pyrene-Tethered Silatranes. (2nd January 2021) - Singh, Gurjaspreet; Singh, Akshpreet; Chowdhary, Kavita; Satija, Pinky; Sanchita,; Kalra, Pooja; Sharma, Geetika; Sinha, Shweta; Sehgal, Rakesh
Abstract: The known silatrane chemistry with polycyclic aromatic hydrocarbons (PAHs) has not been extensively investigated. The current study features synthesis and characterization of silatranes bearing pyrene substituent at the apical silicon site starting from 1-pyrenecarboxaldehyde and N -(3-(trimethoxysilyl)propyl)ethane-1, 2-diamine. The synthesized silatranes were subjected to time-dependent hydrolysis study to examine their hydrolytic stability. In addition, one of the silatrane has been used to entrap nickel chloride to obtain complex of 1:1 composition. Mass, IR spectroscopic data and theoretical study revealed about the chelate structure of the complex in which silatrane acts as a bidentate ligand. The protozoans are cause of numerous infective diseases and so the article also assesses the anti-parasitic potential of the prepared compounds. Both the silatranes showed significant activity against Giardia lamblia and Entamoeba histolytica and very low IC50 values of (6 ) against G. lamblia and (7 ) against E. histolytica indicate their potential to act as efficient drug in comparison to standard drug, metronidazole.